Undergraduates’ perceptions of the value of service-learning - Drewery, Merritt L.; Lollar, Jonathan (Frontiers in Education, 2024)
Service-learning integrates community service with academic study. Students apply skills and knowledge in practical situations and reflect on their experiences. Our 3000-level servicelearning college course, Leadership Development in Agricultural Sciences, involved student-led development and execution of a one-day event, "AgCamp," held on a university campus for high school students. The objective of this study was to evaluate if an intervention (i.e., a servicelearning project) changed undergraduate students' perceptions of their ability to collaborate, ability to lead, and overall perceptions of the usefulness of service-learning. An electronic mixed methods questionnaire-based survey was developed, tested for validity and reliability, and distributed to college students enrolled in Leadership Development in Agricultural Sciences as a pre-and post-test at the beginning and end of two semesters. Data were analyzed in SPSS 26.0 using measures of central tendency and paired sample t-tests. Undergraduate students' (n=74) had positive perceptions of service-learning entering the semester, all measures of which improved as a result of their experiences in the course. In comparison with traditional courses, students felt service-learning courses have more societal benefits and should be increasingly offered. Participating in the service-learning project significantly increased students' comfort working with people from different cultures or backgrounds and empowered them in different ways, including with decision-making. Ultimately, our data indicate that students enjoyed service-learning and received soft skill development through the course. We recommend servicelearning be increasingly integrated into post-secondary curriculum.